Istikhdamu al-Tasykiil Li Tarqiyah Maharah al-Qiraah bi Madrasah Dar al-Salafi - Hindun, Hindun (Al-Wazan: Journal of Arabic Education, 2024)
The reading skill is one of the four language skills and is a key to learning the new language in terms of books, magazines, and the like. Reading Arabic texts is not easy. As for mastering the skill of reading, it means having the ability to understand what is read in a correct and good way. For beginners in learning the Arabic language, reading textbooks and homework without movements is difficult for them because they do not possess and do not know the science of grammar, which is not like reading the Holy Quran. With the passage of time, technology is increasing, and it is known that the role of the media is very important in learning the Arabic language. Experts have provided applications or websites to facilitate learning the Arabic language, including "Tashkeel", which is one of the applications to give movements in electronic media that can be stored on Android phones. This research looks at how to use "tashkeel" to improve reading skills and what is said about its advantages and disadvantages. The approach used in this research is a descriptive study, and to obtain the intended data, the data collection method used is the interview. And the most important results are that one of its advantages is that it facilitates students reading of the Arabic text, and one of its disadvantages is that it often takes time to use it because of the broken network